A permeation-controlled formaldehyde reference source for application in environmental test chambers. (October 2017) - Salthammer, Tunga; Giesen, Ruth; Schripp, Tobias
Abstract: In a wide range of indoor air pollutants, formaldehyde is one of the most-used and best-known substances. In order to protect human health, many countries have established threshold values for the release of formaldehyde from miscellaneous products and revise them constantly. Compliance with these regulations is usually assessed by emission test chamber measurements or derived methods. To control and improve the mechanisms of an emission test chamber, a reliable reference source with sample mimicking emission properties is required but not available so far. This study describes a permeation-controlled reference source based on the application of paraformaldehyde as formaldehyde releasing polymeric compound. Interactions between the formaldehyde release of the source and the governing chamber parameters temperature, relative humidity and air velocity were investigated in 1 m 3 emission chambers. Depending on the conditions, constant formaldehyde concentrations between approximately 10 ppb and 150 ppb can be adjusted for up to 600 h. A linear correlation between the logarithm of the chamber concentration and the reciprocal temperature was found. The results support the feasibility of the source for validation of emission test chamber performance. Graphical abstract: Highlights: This is the first formaldehyde reference source with realistic emission properties. Paraformaldehyde is a suitable polymer for the controlled release of formaldehyde. The principle of the reference source is simple and the design is robust. The formaldehyde emission rate is stable for more than 20 h. The emission behavior of the source can be changed in dependence of temperature and humidity.